MANAJEMEN KURIKULUM BERBASIS CINTA: IKHTIAR MEMBANGUN PENDIDIKAN ISLAM YANG HUMANIS DAN TRANSFORMATIF - Siti Aisyah; Zainal (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
Curriculum management in Islamic education has long been dominated by an administrative–technocratic approach that emphasizes compliance with standards, program effectiveness, and cognitive achievement. Such an orientation tends to marginalize affective and relational dimensions, including values of compassion and care, which are central to the educational process in Islam. Philosophically, Islamic education aims to cultivate the whole person (insan kamil) through a comprehensive process of humanization. Previous studies have largely examined curriculum management from the perspectives of educational quality, religious moderation, or twenty-first-century competencies, yet they have not explicitly positioned love as an institutionalized managerial paradigm within curriculum planning, implementation, and evaluation. This condition indicates a research gap regarding the integration of love as an ethical and pedagogical foundation in Islamic curriculum management. This study offers a novel conceptualization of LoveBased. Curriculum Management, which frames love (mahabbah and rahmah) not merely as an individual emotional value, but as a guiding managerial principle that shapes curriculum policy, educational relationships, and the orientation of educational goals. The urgency of this research is further reinforced by the contemporary crisis of empathy, the increasing prevalence of symbolic violence in educational practices, and the growing demand for Islamic education capable of transforming learners’ intellectual, moral, and social consciousness. Employing a qualitative approach through a literature review, this study examines works on Islamic educational management, Paulo Freire’s humanistic pedagogy, and the educational thought of classical Muslim scholars such as Al-Ghazali and Ibn Miskawaih, particularly their emphasis on ethics and compassion in education. The findings indicate that love-based curriculum management is able to reorient education from a mere transfer of knowledge toward character formation, strengthen dialogical relationships between educators and learners, and foster the transformation of Islamic education into a more just, inclusive, and meaningful system. Keywords: curriculum management, Islamic education, love, humanism, educational transformation.